2010
DOI: 10.1074/jbc.m109.074393
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Spliceosomal U4 Small Nuclear RNA in Heterochromatic Gene Silencing at Fission Yeast Centromeres

Abstract: prp13-1 is one of the mutants isolated in a screen for defective pre-mRNA splicing at a nonpermissive temperature in fission yeast Schizosaccharomyces pombe. We cloned the prp13 ؉ gene and found that it encodes U4 small nuclear RNA (snRNA) involved in the assembly of the spliceosome. The prp13-1 mutant produced elongated cells, a phenotype similar to cell division cycle mutants, and displays a high incidence of lagging chromosomes on anaphase spindles. The mutant is hypersensitive to the microtubule-destabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 37 publications
3
59
0
Order By: Relevance
“…However, this Raf2–Rik1 complex seems to be distinct from the CLRC complex, and direct evidence of cooperation between the RNAi and DNA replication machineries is lacking. It has also been proposed that the splicing machinery contributes to heterochromatic silencing by directly interacting with the RDRC and the nascent transcript platform to promote siRNA biogenesis 43,44 . However, earlier biochemical purifications demonstrated that the RDRC subunit Cid12 forms RDRC-independent complexes with splicing factors 27 .…”
Section: Rnai-mediated Heterochromatin Assemblymentioning
confidence: 99%
“…However, this Raf2–Rik1 complex seems to be distinct from the CLRC complex, and direct evidence of cooperation between the RNAi and DNA replication machineries is lacking. It has also been proposed that the splicing machinery contributes to heterochromatic silencing by directly interacting with the RDRC and the nascent transcript platform to promote siRNA biogenesis 43,44 . However, earlier biochemical purifications demonstrated that the RDRC subunit Cid12 forms RDRC-independent complexes with splicing factors 27 .…”
Section: Rnai-mediated Heterochromatin Assemblymentioning
confidence: 99%
“…While we cannot exclude that defective splicing of some other contributory factor might be involved, we instead sought further evidence of a direct role of splicing components in processing of centromeric transcripts. Two previous studies have reported evidence of splicing of centromeric transcripts [44,45]. To confirm this and investigate the sensitivity of these splicing events to splicing mutants, we analysed centromeric transcripts by RT-PCR.…”
Section: Deletion Of Splicing-associated Factors Affects Rnai-dependementioning
confidence: 99%
“…The TRAMP complex regulates centromeric silencing by processing centromeric transcripts and promoting their degradation by the exosome (Buhler et al 2007;Reyes-Turcu et al 2011). Splicing has also been implicated in heterochromatin formation in S. pombe (Bayne et al 2008;Chinen et al 2010;Lee et al 2013). The NURS complex subunits Red1, Mtl1, Iss10, and Red5 are required for both meiotic mRNA degradation and H3K9 methylation at meiotic genes (Figs.…”
Section: The Nurs Complex and Histone H3k9 Methylationmentioning
confidence: 99%